Hexavalent Chromium Removal by a Paecilomyces sp. Fungal Strain Isolated from Environment - Juan F. Cárdenas-González; Ismael Acosta-Rodríguez (Bioinorganic Chemistry and Applications)
A resistant and capable fungal strain in removing hexavalent chromium was isolated from an environment near of Chemical Science Faculty, located in the city of San Luis Potosí, Mexico. The strain was identified as Paecilomyces sp., by macro- and microscopic characteristics. Strain resistance of the strain to high Cr (VI) concentrations and its ability to reduce chromium were studied. When it was incubated in minimal medium with glucose, another inexpensive commercial carbon source like unrefined and brown sugar or glycerol, in the presence of 50 mg/L of Cr (VI), the strain caused complete disappearance of Cr (VI), with the concomitant production of Cr (III) in the growth medium after 7 days of incubation, at 28∘C, pH 4.0, 100 rpm, and an inoculum of 38 mg of dry weight. Decrease of Cr (VI) levels from industrial wastes was also induced by Paecilomyces biomass. These results indicate that reducing capacity of chromate resistant filamentous fungus Cr (VI) could be useful for the removal of Cr (VI) pollution.